VD_FINDINFO Jug / 2011 / 211 vom 18. Mai 2011 - VD Tribunal cantonal (2011)
IN DUBIO PRO REO, FIXATION DE LA PEINE, AGGRAVATION DE LA PEINE, VOLDROIT PÉNAL, DOMMAGE MATÉRIEL | 27 al. 1 CP, 27 al. 2 CP, 43 CP, 47 CP